2010
DOI: 10.1002/marc.200900698
|View full text |Cite
|
Sign up to set email alerts
|

The Advantages of In Situ Surfactant Generation for Miniemulsions

Abstract: The stabilisation of miniemulsions using an in situ generated surfactant is presented. This surfactant, prepared from of a water-soluble base and an oil-soluble long chain acid was successfully used to create stable miniemulsions with up to 60 vol.-% organic phase. It is shown that the creation of a surface active species at the oil-water interface allowed stable miniemulsions to be generated more rapidly than when using conventional surfactant. In addition, polymerised miniemulsions exhibited less secondary n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 11 publications
2
40
0
Order By: Relevance
“…[19] A recent investigation from our group suggests that increasing the base to acid ratio by 50% (to a ratio of 3:2) allows us to successfully produce and polymerise miniemulsions. [20] Building on these promising results, the objective of the work presented here is to investigate the efficiency and robustness of in situ surfactants in the production and polymerisation of miniemulsion droplets. First we contrast the performance of in situ to preformed surfactants in terms of homogenisation time using a rotor-stator in order to investigate whether or not using in situ surfactant changes the dynamics of droplet stabilisation.…”
Section: Introductionmentioning
confidence: 99%
“…[19] A recent investigation from our group suggests that increasing the base to acid ratio by 50% (to a ratio of 3:2) allows us to successfully produce and polymerise miniemulsions. [20] Building on these promising results, the objective of the work presented here is to investigate the efficiency and robustness of in situ surfactants in the production and polymerisation of miniemulsion droplets. First we contrast the performance of in situ to preformed surfactants in terms of homogenisation time using a rotor-stator in order to investigate whether or not using in situ surfactant changes the dynamics of droplet stabilisation.…”
Section: Introductionmentioning
confidence: 99%
“…Miniemulsions were prepared based on the in situ surfactant generation technique [38][39][40]42,43] in combination with ultrasonication. Conventional radical polymerizations of styrene in miniemulsion initiated by AIBN at 70 8C were conducted based on the recipes in Table 1.…”
Section: Miniemulsion Preparationmentioning
confidence: 99%
“…[41] High energy mechanical homogenization devices in tandem with the in situ surfactant technique results in more rapid production of a given droplet diameter than when using a preformed surfactant. [42,43] The present Communication describes a novel miniemulsion polymerization approach for synthesis of nanosized polymer particles by combination of the in situ surfactant generation technique and high-energy homogenization at relatively high surfactant content. This technique enables synthesis of polymeric nanoparticles with diameters as low as <20 nm in a one-step process (no monomer feed) using considerably less surfactant than a microemulsion system.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been demonstrated that surfactant generation at the interface combined with high-energy miniemulsification results in more rapid generation of a given droplet size than with preformed surfactant. 31,32 Under unsuitable conditions (in terms of ratio of base to acid and amount of surfactant generated), the in situ surfactant technique results in systems that proceed mainly via an emulsion polymerization mechanism. 33 We have reported that the in situ surfactant technique can also be successfully applied to nitroxide-mediated radical polymerization.…”
Section: Introductionmentioning
confidence: 99%